The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1159/000028791
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-Guided Proximal Catheter Placement in Treatment of Posterior Fossa Cysts

Abstract: Purpose: Treatment of posterior fossa cysts by cystoperitoneal shunting may be complicated by a malpositioned proximal catheter located within the brainstem or cerebellum causing acute shunt malfunction or neurological deficits. We propose that proximal catheter placement from a posterior fossa approach aided by a malleable endoscope may prevent malposition and its complications. Methods: We present 4 procedures we performed on 3 patients with posterior fossa cysts using a posterior fossa approach. In each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Treatment of retroclival or intra-fourth ventricular PFAC by cystoperitoneal shunting may be complicated by a malpositioned proximal catheter located within the brainstem or cerebellum causing acute shunt malfunction or neurological deficits. [ 22 ] Sandberg and Souweidane[ 23 ] suggested that proximal catheter placement from a posterior fossa approach can be aided by a malleable endoscope that may prevent malposition and its complications as observed in 3 out of their 4 cases they treated by using this technique. Hence, we suggest this to be performed only by experts in the neuro-endoscopic field.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of retroclival or intra-fourth ventricular PFAC by cystoperitoneal shunting may be complicated by a malpositioned proximal catheter located within the brainstem or cerebellum causing acute shunt malfunction or neurological deficits. [ 22 ] Sandberg and Souweidane[ 23 ] suggested that proximal catheter placement from a posterior fossa approach can be aided by a malleable endoscope that may prevent malposition and its complications as observed in 3 out of their 4 cases they treated by using this technique. Hence, we suggest this to be performed only by experts in the neuro-endoscopic field.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,19 There have even been endorsements of CT-guided insertion of the catheter in a two-stage proce-dure. 11,13,19 There have even been endorsements of CT-guided insertion of the catheter in a two-stage proce-dure.…”
Section: Discussionmentioning
confidence: 99%
“…Different endoscopic techniques may be applied to the surgery of infratentorial arachnoid cysts, including endoscopic cyst fenestration through a burr hole [2,9,12,15,20,23], endoscope-assisted or endoscope-controlled microneurosurgery [12,13], and endoscope-guided proximal catheter placement [22].…”
Section: Discussionmentioning
confidence: 99%